Risk assessment and management in Malaysian teacher training programmes - Syed Abdullah, Sharifah Intan Sharina; Mohamad Nasri, Nurfaradilla; Mohd Ayub, Ahmad Fauzi (Fakultas Ilmu Tarbiyah dan Keguruan, UIN Syarif Hidayatullah Jakarta, 2017)
Risk assessment and management is commonly discussed in the literature of outdoor education. This is because being surrounded with higher risks is one of the nature of its implementation and features that distinguished outdoor education from indoor learning. In this paper, we suggest that risk may occur everywhere, indoor and outdoor, and risk assessment and management should be carried out by all educators regardless the approach and the venue of learning. Following this suggestion, further implication of this paper is a suggestion to develop new curriculum on risk assessment and management for all fields in teacher training programmes.